COMMUNICATION STRATEGY OF DAKWAH IN ONLINE MEDIA: A COMPARATIVE STUDY BETWEEN KH BAHAUDDIN NURSALIM AND USTADZ SYAFIQ RIZA BASALAMAH ON THE YOUTUBE CHANNEL - Riszalatul Khasanah (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2023)
Da'wah on social media is a strategy carried out by preacher as a form of litera media and explore the period. With the form of language style, gestures, intonation, selection the theme to understand the character of each area that wants to be a place of preaching. Al-Qur'an and Hadith are guidelines in preaching. Therefore, the researcher did comparative research of national preacher who preaches on social media, especially YouTube media, namely KH Bahauddin Nursalim and Ustadz Syafiq Riza Basalamah. Both characters have characteristics in preaching, which is liked by the community ranging from teenagers, adults, to old people. Some of the aphorisms in the study that are spoken will be written by the public and even on the internet upload it on social media. The focus of the research is how the da'wah communication strategy of KH Bahauddin Nursalim and Ustadz Syafiq Riza Basalamah on the youtube channel and how the effect of da'wah on society.